Motor auto repair manual 1988 - Motor (New York, N.Y. : Motor, 1987)
"This manual covers mechanical specifications and service procedures on 1982-88 models available at time of its publication. This manual is divided into five sections using four tabs. The section before tab 1 covers Gasoline Engine Tune Up Specifications, Diesel Engine Performance Specifications and Troubleshooting. The section in Tab 1 covers American Motors vehicles; the section in Tab 2 covers Chrysler Motors/vehicles; the section in Tab 3 covers Ford Motor Co. vehicles; and the section in Tab 4 covers General Motors Corporation vehicles."
English text.
SERBIB/SERLOC merged record
Keywords: Automobiles -- Maintenance and repair -- Periodicals; Automobiles -- Maintenance and repair; Periodicals; Nonfiction; Periodicals